Implementation of the Customs Digital Transformation Policy Using the Ceisa 4.0 System to Improve Customs and Excise Services - Rahmi, Notika; Arimbhi, Pebriana; Dartono (Yayasan Ilomata, 2025)
The Directorate General of Customs and Excise is evolving the information technology system. Since the introduction of the Customs Fast Release System (CFRS), the CEISA 4.0 application has been used. The CEISA 4.0 application continues to be developed to improve customs and excise services. This means that internal and external policymakers must continue adapting to changes in existing applications. This makes us research to analyse the implementation, obstacles, and efforts involved in implementing the CEISA 4.0 system. The research method used is qualitative analytical descriptive with data collection techniques of observation, interviews and documentation. Interviews were conducted with 20 informants: Customs, Platform Providers and Service Users. The research results show that the implementation of CEISA 4.0 is still under development and is not fully running perfectly because there are still business processes that are not/have not been touched by the CEISA 4.0 program. In some cases, bugs are still encountered and/or system stability has not been properly maintained. However, it has been running efficiently where customs and excise obligations are fulfilled paperless; it can be done anytime and anywhere. The HR capabilities of DJBC and service users still require training in operating CEISA 4.0 because several tools are not yet familiar regarding the standards, policy targets and characteristics of the implementing organisation, namely that the implementation of the rules has gone well using a clear legal basis and rules.